Valuing diversity: CEOs' career experiences and corporate investment - Hu, Conghui; Liu, Yu-Jane (Journal of Corporate Finance, 2015)
This paper investigates the impact of CEOs' career experiences on corporate investment decisions. We hypothesize that CEOs with more diverse career experiences are less likely to be constrained by insufficient internal capital. The potential mechanism is that rich external experiences help CEOs accumulate social connections and these connections mitigate information asymmetry and lead to better access to external funds. Consistent with this argument, we find that firms with CEOs who have more diverse career experiences exhibit lower investment-cash flow sensitivity and exploit more outside funds, including both bank loans and trade credit. These effects are more pronounced among financially constrained firms. Even controlling for connections gained through financial institutions or government offices, the effect of diversity still remains very strong. Finally, we conduct several tests to mitigate the concern that our results are driven by the endogeneity of CEOs' appointments.